2021
DOI: 10.1093/qjmed/hcab142
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab in the treatment of COVID-19—a meta-analysis

Abstract: Objective To evaluate whether IL-6 inhibitor tocilizumab (TCZ) reduces mortality among hospitalized COVID-19 patients. Methods Systematic review and meta-analysis of randomized controlled trials (RCTs) comparing TCZ versus placebo/control, for treatment of adults with COVID-19. Primary outcome was 28-30 days all-cause mortality. Search was conducted up to April 1st 2021. Two independent reviewers screened citations, extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 27 publications
1
20
0
6
Order By: Relevance
“…Consistent with our findings, recent meta-analyses of randomized trials exploring the effect of tocilizumab treatment in patients with COVID-19 showed a favourable effect on mortality risk [ 31–35 ]. Some meta-analyses suggested that tocilizumab treatment had no significant positive effect on mortality, but these studies included non-randomized trials [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our findings, recent meta-analyses of randomized trials exploring the effect of tocilizumab treatment in patients with COVID-19 showed a favourable effect on mortality risk [ 31–35 ]. Some meta-analyses suggested that tocilizumab treatment had no significant positive effect on mortality, but these studies included non-randomized trials [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…A prospective meta-analysis of randomized trials showed reduced 28-day all-cause mortality with the use of IL-6 antagonists in COVID-19 [ 83 ]. A meta-analysis demonstrated that tocilizumab is associated with reduced 30-day mortality, ICU admissions, mechanical ventilation, and superinfection rates in patients with COVID-19 not admitted to the ICU [ 84 ]. A randomized clinical trial of tocilizumab for the treatment of COVID-19 specifically in patients with cancer and COVID-19 (NCT04370834) was stopped prematurely after only enrolling 1 patient [ 81 ].…”
Section: Covid-19 Therapeutics In Patients With Hematologic Malignanciesmentioning
confidence: 99%
“…Anti-inflammatory treatment with dexamethasone was shown to reduce mortality in patients hospitalized with COVID-19 and requiring respiratory support (5). Subsequent trials have shown possible clinical benefit of the interleukin-6 (IL-6) inhibitors tocilizumab and sarilumab (6)(7)(8)(9)(10) and of the Janus kinase (JAK) inhibitors baricitinib and tofacitinib (11)(12)(13), both with and without concurrent steroid treatment (11)(12)(13)(14)(15)(16), although data are not dispositive. Despite this uncertainty, current guidelines for anti-inflammatory therapy recommend tocilizumab or baricitinib, and recommend sarilumab or tofacitinib as alternatives (17).…”
mentioning
confidence: 99%